EMPIRICAL MODELS RESEARCH AND COMPETITIVENESS OF PERSONALITY CHARACTERISTICS PSYCHODIAGNOSTICS - Zhovner, Vitaliy (PSYCHOLOGICAL JOURNAL, 2017)
The article analyzes the scientific approaches of psychodiagnostic research tools for individual psychological characteristics that determine personality competitiveness. We applied general principles of scientific research: principle of systematic approach to personality understanding, vision of individual as an active subject of activity, principles of determinism and development, unity of consciousness and activity of the individual, principle of psychological activity theory, principle of multimotiveted entrepreneurship activity, life and professional personal development, methodological principles of psychological research organization, patterns of biological and social value in the human mind, concept of genetic-modeling research method for entrepreneur personality. The study is based on genetic-modeling method with the following principles: principle of «analysis per unit», principle of «biological and social unity», principle of «creativity», principle of «reflexive relativism», principle of «experimental and genetic lines of development unity». We developed and revealed the content of empirical research model and specified personality determinants of competitiveness including such units as organization (stages), theoretical and methodological basis of individual competitiveness research, external and internal factors, psychodiagnostic set of techniques and components of competitiveness development.